2015
DOI: 10.1007/s00330-015-3854-5
|View full text |Cite
|
Sign up to set email alerts
|

MR appearance of parathyroid adenomas at 3 T in patients with primary hyperparathyroidism: what radiologists need to know for pre-operative localization

Abstract: 3 T MRI protocol based on T2-weighted IDEAL FSE sequences was used. T2-hyperintensity and elongated morphology are common features of PTAs. 3 T MRI could be used in the preoperative detection of PTAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…MR imaging alone has been shown to allow accurate localization of abnormal parathyroid glands (12,26). Because of the lack of adipose tissue in parathyroid adenomas, high signal intensity on T2-weighted images is seen typically at MR imaging, which enables detection of adenomas (27). Because of advances in technology, its accuracy has increased even further with the use of dynamic contrast materialenhanced imaging (16).…”
Section: Discussionmentioning
confidence: 99%
“…MR imaging alone has been shown to allow accurate localization of abnormal parathyroid glands (12,26). Because of the lack of adipose tissue in parathyroid adenomas, high signal intensity on T2-weighted images is seen typically at MR imaging, which enables detection of adenomas (27). Because of advances in technology, its accuracy has increased even further with the use of dynamic contrast materialenhanced imaging (16).…”
Section: Discussionmentioning
confidence: 99%
“…MRI can also be used to localize parathyroid glands. Evidence remains scarce, but one of the largest studies so far showed a sensitivity of 82 % with a PPV of 89 % and a very recent publication also showed promising results [51, 52]. Considering the unique benefits of 18F-FCH PET and MRI, a potentially superior modality would be using the 18F-FCH tracer and a combined PET MRI scanner.…”
Section: Discussionmentioning
confidence: 99%
“…The use of MRI allows the evaluation of parathyroid anatomy, detection of ectopic glands, in the absence of patient's radiation exposure; reported sensitivity is 80% with the 1.5 T magnets (14). Better visualization has recently been obtained with the use of 3.0 T MRI magnet as a valid method for parathyroid lesions identification, particularly in PHPT patients with negative first-line imaging (15,16 About 30 years ago, when we started to be interested in PHPT (17), the only clinical task was to make the diagnosis. Imaging of the parathyroid glands was an almost unexplored field and patients were immediately referred to the surgeon with expertise in neck operation.…”
Section: Introductionmentioning
confidence: 99%